2010
DOI: 10.1007/s11426-010-0130-z
|View full text |Cite
|
Sign up to set email alerts
|

The design and synthesis of fused thiophenes and their applications in organic field-effect transistors

Abstract: Fused thiophenes refer to oligothienoacenes in which several thiophenes are coupled together via two-or multi-positions and their derivatives. The synthesized organic semiconductors based on fused thiophenes exhibit excellent field effect properties due to their efficient intermolecular SS interactions and  stacking. The performances of organic field-effect transistors (OFETs) depend not only on the materials but also on the devices. Such factors which influence the device performances as device structur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 102 publications
0
3
0
Order By: Relevance
“…1–10 Organic semiconductors are promising for many potential applications, including phototransistors, 11,12 integrated circuits, 13–15 displays, 16–18 electronic papers, 19,20 radio frequency identification (RFID) tags, 21,22 sensors, 23–26 electronic skins, 27–29 storage devices, 30–32 molecular magnets, 33–35 lasers 36–38 and masers. 39,40 Synthetic chemists have created a large library of organic semiconductors with excellent electronic properties, such as oligothiophenes, 41,42 heteroacenes, 43–46 thienoacenes, 47,48 tetrathiafulvalenes, 49,50 metal phthalocyanines, 51–53 porphyrins, 54,55 fullerenes, 56,57 and conjugated polymers. 58–60 Among them, some linearly condensed acenes present high mobilities owing to their extended π-conjugation and enhanced intermolecular π–π overlapping.…”
Section: Introductionmentioning
confidence: 99%
“…1–10 Organic semiconductors are promising for many potential applications, including phototransistors, 11,12 integrated circuits, 13–15 displays, 16–18 electronic papers, 19,20 radio frequency identification (RFID) tags, 21,22 sensors, 23–26 electronic skins, 27–29 storage devices, 30–32 molecular magnets, 33–35 lasers 36–38 and masers. 39,40 Synthetic chemists have created a large library of organic semiconductors with excellent electronic properties, such as oligothiophenes, 41,42 heteroacenes, 43–46 thienoacenes, 47,48 tetrathiafulvalenes, 49,50 metal phthalocyanines, 51–53 porphyrins, 54,55 fullerenes, 56,57 and conjugated polymers. 58–60 Among them, some linearly condensed acenes present high mobilities owing to their extended π-conjugation and enhanced intermolecular π–π overlapping.…”
Section: Introductionmentioning
confidence: 99%
“…Dithienothiophene (DTT) derivatives, as analogues of acenes, have shown considerable mobility. [35][36][37][38][39][40][41][42][43][44][45][46][47][48] For these fused thiophene structures, there may exist various intermolecular interactions including weak hydrogen bonding, p-p stacking, C-H interactions, and S-S interactions. In our previous studies, it was found that the introduction of the CQC double bond can lead to the formation of S-p intermolecular interaction and is responsible for a high m of 2.…”
Section: Introductionmentioning
confidence: 99%
“…In the course of development of suitable π-conjugated molecules used as p -channel organic semiconductor materials, many ladder-type molecules have been intensively studied, particularly acene- and thienoacene-based molecules . Recently, different isomers of thienoacenes have received considerable attention because of their topology of planar frameworks and highly delocalized electronic structures, which make them good candidates for applications in organic field-effect transistors (OFETs) .…”
mentioning
confidence: 99%